A Systematic Review Of The Integration Of 21st-Century Skills And Educational Technology For The Career Development Of Islamic Education Teachers - Darmanto; Yulia Wahyuni; Muhammad Sirozi (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2026)
The integration of 21st-century skills and educational technology has become a critical issue in improving the quality of Islamic Education (PAI) and supporting teacher career development in the digital era. This study aims to analyze how the integration of the Four Cs critical thinking, creativity, collaboration, and communication and educational technology contributes to the professional growth of PAI teachers and the transformation of learning practices. This research employs a qualitative approach using a systematic literature review method, analyzing selected scholarly articles published between 2020 and 2025. Data were collected through structured searches in academic databases and analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings indicate that the integration of 21st-century skills and educational technology enhances teachers’ pedagogical competence, promotes innovative and student-centered learning, and expands professional opportunities through digital engagement and scholarly activities. However, critical reflection reveals inconsistencies in previous studies, particularly in the gap between theoretical frameworks and classroom implementation, as well as the uneven impact of technology integration due to variations in teacher readiness and institutional support. Additionally, most studies focus on short-term outcomes, leaving a gap in understanding long-term career development. This study concludes that the integration of 21st-century skills and educational technology is essential but requires comprehensive and systemic support to be effectively implemented. The research contributes by providing an integrative framework that links competencies, technology, and career development, offering both theoretical insights and practical implications for advancing PAI education in the digital era.